TELOS Feasibility Analysis for Application Development Project using System Dynamics Approach - Putri, Sinta Mulyani Dwi; Chumaidiyah, Endang; Sriwana, Iphov Kumala (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
Organization X reported that 75% of its application development projects from 2020 to 2023 were overscheduled, with the ABC application project being the most delayed. Field observations attributed these failures to inadequate planning and the absence of structured feasibility evaluations. This study addresses the gap by designing a dynamic feasibility model for the ABC project using a System Dynamics (SD) approach grounded in the TELOS criteria—Technical, Economic, Legal, Operational, and Scheduling. Unlike traditional static methods, the SD model captures feedback loops and interdependencies between project variables, enabling dynamic scenario simulations. Applied research methods were used to develop causal loop and stock flow diagrams, which were verified and validated via the Vensim tool. Baseline simulations yielded an average feasibility score of 7.26, exceeding the viability threshold. Among four tested scenarios, a combined intervention—adding 30%-time reserve, increasing team size, and enhancing quality control—produced the highest score of 7.35. Singular adjustments to time, cost, or quality were less effective than the integrated approach. This study demonstrates the novelty and effectiveness of applying SD to TELOS-based feasibility analysis, offering a predictive and adaptive tool for strategic project planning. The model enables proactive identification of critical phases and supports more informed decision-making, improving alignment with organizational objectives and overall project success. Keywords: Project Feasibility, TELOS, Dynamic Systems, Decision Making, Project Management